Nanocomposite bone scaffold - Abu Bakar @ Zakaria, Md Zuki; Bharatnam, B. Hemabarathy; Mohamad Yusof, Loqman (2013)
The present invention relates to a nanocomposite bone scaffold and a method for preparing nanocomposite bone scaffold. The nanocomposite bone scaffold comprises of; nanoparticles Calcium Carbonate from Cockle shell, and alginate. Advantageously, the nanocomposite bone scaffold is usable as fracture void fillers to facilitate bone growth in order to shorten healing period.